The unintended consequences of school inspection: the prevalence of inspection side-effects in Austria, the Czech Republic, England, Ireland, the Netherlands, Sweden, and Switzerland. (2nd November 2017) - Jones, Karen L.; Tymms, Peter; Kemethofer, David; O'Hara, Joe; McNamara, Gerry; Huber, Stephan; Myrberg, Eva; Skedsmo, Guri; Greger, David
Abstract: It has been widely documented that accountability systems, including school inspections, bring with them unintended side effects. These unintended effects are often negative and have the potential to undo the intended positive effects. However the empirical evidence is limited. Through a European comparative study we have had the rare opportunity to collect empirical evidence and study the effects (both intended and unintended) of school inspections (a key system of accountability) in a systematic way, across seven countries. We present the findings of the unintended effects in this paper. Survey self-report responses from school principals in each country, with differing school inspection systems, are analysed to measure the prevalence of these unintended effects and to investigate the part played by pressure to do well in inspections. A key finding is that increasing pressure in school inspection systems is associated with the undesired effect of the narrowing and refocusing of the curriculum and instructional strategies. We also show that a proportion of school principals admit to misrepresenting the school in data sent to the inspectorate and show evidence for formalisation/proceduralisation (excessive focus on records) and ossification (fear of experimentation in teaching), although these factors are less related to changes in pressure.